Getting Real: Aligning the Learning Needs of Clerkship Students With the Current Clinical Environment. (January 2019) - Klamen, Debra L.; Williams, Reed; Hingle, Susan
Abstract : The authors present follow-up to a prior publication, which proposed a new model for third-year clerkships. The new model was created to address deficiencies in the clinical year and to rectify a recognized mismatch between students' learning needs and the realities of today's clinical settings. The new curricular model was implemented at Southern Illinois University School of Medicine in academic year 2016–2017. Guiding principles were developed. These were to more deeply engage students in experiential learning through clinical immersion; to pair individual faculty with individual students over longer periods of time so real trust could be developed; to provide students with longitudinal clinical reasoning education under controlled instructional conditions; to simplify goals and objectives for the core clerkships and align them with student learning needs; and to provide students with individualized activities to help them explore areas of interest, choose their specialty, and improve areas of clinical weakness before the fourth year. The authors discuss reactions by faculty and students to the new curriculum, which were mostly positive, as well as several outcomes. Students showed very different attitudes toward what they defined as success in the clerkship year, reflective of their deeper immersion. Students spent more time working in clinical settings and performed more procedures. Performance on Step 2 Clinical Knowledge and Clinical Skills was unchanged from traditional clerkship years. The 2015 article called for rethinking the third-year clerkships. The authors have shown that such change is possible, and the new curriculum can be implemented with successful early outcomes.